Sub-Doppler spectroscopy with an external cavity quantum cascade laser - Walker, R; Kirkbride, J; van Helden, J; Weidmann, D; Ritchie, G (2013)
The linewidth of an external cavity quantum cascade laser is studied as a function of injection current and laser scan rate. The laser linewidth is inferred to be ca. 2.5 MHz from Lamb-dip spectra on a low pressure sample of NO and its variation with injection current is well modeled using literature values for the intrinsic material properties of the lasing medium. The laser linewidth measurements are corroborated by polarization spectroscopy studies as well as by analysis of hyperfine structure and cross-over resonances. © 2013 Springer-Verlag Berlin Heidelberg.